Pengaruh Inflasi dan Bagi Hasil Terhadap Deposito Mudharabah (Studi Kasus Pada Pt. Bank Syariah Mandiri) - Putu Tirta Sari Ningsih; Devi Ambarsari (Universitas Mohammad Husni Thamrin, 2020)
This study aims to determine the effect of Inflation and Profit Sharing Mudharabah Deposits at PT. Syariah Mandiri. Mudharabah deposits are fund deposits with a scheme of fund owners entrusting their funds to be managed by the bank with the results obtained divided between the fund owner and the bank with an agreed ratio from the beginning. Inflation is the tendency of prices to increase in general and continuously. Profit sharing is the amount of income received by the customer based on the profit provided by the bank. This research method is quantitative research with descriptive design. The research was conducted by looking for secondary data and the data used was time series data. The research data was processed by statistical analysis by classical assumption, linear regression analysis and hypothesis testing using IBM SPSS version 22. The results of this study indicate that inflation and profit sharing are simultaneously influential and significant to mudharabah deposits of PT. Bank Mandiri Syariah. When tested partially, inflation has no effect and is not significant on mudharabah deposits of PT. Bank Mandiri Syariah and the effect sharing and significant effect on mudharabah deposits of PT. Bank Mandiri Syariah.From the research that has been carried out for Bank Mandiri Syariah, it is advisable to pay more attention to the company's management in determining the profit sharing policy for mudharabah deposits to be more competitive. From the research that has been done for Bank Mandiri Syariah, it is advisable to pay more attention to the company's management in determining the profit sharing policy.Keywords: Deposits, Mudharabah, Inflation, Profit Sharing.